2021
DOI: 10.1111/bph.15528
|View full text |Cite
|
Sign up to set email alerts
|

Methoxphenidine (MXP) induced abnormalities: Addictive and schizophrenia‐related behaviours based on an imbalance of neurochemicals in the brain

Abstract: Background and Purpose Methoxphenidine is a dissociative‐based novel psychoactive designer drug. Although fatal accidents from methoxphenidine abuse have been reported, recreational use of the drug continues. We aim to provide scientific supportfor legal regulation of recreational abuse of methoxphenidine by demonstrating its the pharmacological action. Experimental Approach Addictive potential of methoxphenidine was examined using intravenous self‐administration test with rats and conditioned place preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…In experiments in rodents focused on the chronic administration of methoxphenidine, Hur et al observed hyperactivity, increased impulsivity, recognition memory dysfunction, social withdrawal, depressive-like behaviour and schizophrenia-relevant symptoms. 9 Compared to controls the MXP treated animals had significantly increased expression levels of CAMK2, DAT (dopamine transporter, SLC6A3), p-DAT, D 1 receptor, and TH and an increase in the p-DAT/DAT ratio. In comparison to its structural analogue diphenidine, MXP is a slightly less potent inhibitor of NET and a significantly less potent inhibitor of DAT.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In experiments in rodents focused on the chronic administration of methoxphenidine, Hur et al observed hyperactivity, increased impulsivity, recognition memory dysfunction, social withdrawal, depressive-like behaviour and schizophrenia-relevant symptoms. 9 Compared to controls the MXP treated animals had significantly increased expression levels of CAMK2, DAT (dopamine transporter, SLC6A3), p-DAT, D 1 receptor, and TH and an increase in the p-DAT/DAT ratio. In comparison to its structural analogue diphenidine, MXP is a slightly less potent inhibitor of NET and a significantly less potent inhibitor of DAT.…”
Section: Introductionmentioning
confidence: 92%
“…10,11 According to unofficial user experiences, MXP is less active than common arylcyclohexylamines like methoxetamine, deschloroketamine or ketamine, 12,13 yet it may be quite addictive. 9,14–16 Despite the lower potency, several intoxications were associated with this substance to date. 12,13 Symptoms like rhabdomyolysis, ischemic cerebral disease, acute kidney failure or other serious psychic and somatic complications can also occur during the intoxications.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animals were selected on the basis of previous studies with consideration of the sensitivity to each behavioural experiment [32]. Studies were designed to generate equally sized groups using randomization.…”
Section: Animalsmentioning
confidence: 99%
“…This test was performed to determine whether Mepirapim treatment changed neurotransmitter levels in each brain region (VTA and NAc). Minor modifications were made to the previously reported experimental design [32]. Brain samples from mice treated with the vehicle or Mepirapim (1 or 3 mg•kg −1 ) during the CPP and tetrad tests were used (n = 5 per group).…”
Section: Neurotransmitter Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…MXP in combination with other dissociatives may lead to delusions, sedation, amnesia, nausea, and even respiratory depression [22]. Moreover, likewise, with other dissociative anesthetics [24,25], methoxphenidine may also be addictive [22,26,27] and may produce various symptoms related to schizophrenia [26]. Yet, even though it has already been available on the black market for at least half a decade, there remains a lack of information on its pharmacological and physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%